RELIGION GAP IN FAMILY (STUDY OF COMMUNITY OF SINGKAWANG CITY WEST KALIMANTAN) - Amalia Irfani (Raheema, 2019)
There are so many social impacts in marriages of different religions and cultures. For example, the problem of education, or the religiousness of children which can change at any time and can not be controlled when the child faces social problems. This paper illustrates how the family life of the multicultural society in West Kalimantan in Singkawang City which is married in different religion but until the end of life remains harmonious. Using the communication psychology approach and the Psychological Theory of Piaget's Cognitive Development . Data obtained through observation, interviews and documentation. According to the research, the differences are caused by cultures brought down from generation to generation, the existence of relentlessness and the ability to adapt to change when the child has decided to choose a religion, parents of different religions tend to be prepared for the consequences of being different religious families. There is also unique finding from this study, that interpersonal communication is effective in establishing intimate and harmonious relationships but has not been able to reduce the inner conflict experienced by child informants as children of couples of different religious parent. In addition, harmonious relationships do not guarantee the success and effectiveness of children in making decisions. Keywords: parents parenting, families of different religions, decision making Ada begitu banyak dampak sosial dalam pernikahan dari berbagai agama dan budaya. Misalnya, masalah pendidikan, atau religiusitas anak yang dapat berubah setiap saat dan tidak dapat dikendalikan ketika anak menghadapi masalah sosial. Makalah ini menggambarkan bagaimana kehidupan keluarga masyarakat multikultural di Kalimantan Barat di Kota Singkawang yang menikah di berbagai agama tetapi sampai akhir hayat tetap harmonis. Menggunakan pendekatan psikologi komunikasi dan Teori Psikologis Perkembangan Kognitif Piaget. Data diperoleh melalui observasi, wawancara dan dokumentasi. Menurut penelitian, perbedaan itu disebabkan oleh budaya yang diturunkan dari generasi ke generasi, keberadaan tanpa belas kasihan dan kemampuan untuk beradaptasi terhadap perubahan ketika anak telah memutuskan untuk memilih agama, orang tua dari berbagai agama cenderung siap untuk konsekuensi. menjadi keluarga agama yang berbeda. Ada juga temuan unik dari penelitian ini, bahwa komunikasi interpersonal efektif dalam membangun hubungan yang intim dan harmonis tetapi belum mampu mengurangi konflik batin yang dialami oleh informan anak sebagai anak-anak dari pasangan pasangan orang tua yang berbeda agama. Selain itu, hubungan yang harmonis tidak menjamin kesuksesan dan efektivitas anak dalam membuat keputusan. Kata kunci: pengasuhan orang tua, keluarga dari berbagai agama, pengambilan keputusan